Colorimetric detection of ascorbic acid and alkaline phosphatase activity based on the novel oxidase mimetic of Fe–Co bimetallic alloy encapsulated porous carbon nanocages - Wu, Tengteng; Ma, Zhangyan; Li, Peipei; Liu, Meiling; Liu, Xiaoying; Li, Haitao; Zhang, Youyu; Yao, Shouzhuo (Talanta (Oxford), 2019)
A novel catalyst of FeCo nanoparticles (FeCo NPs) incorporated porous nanocages (FeCo NPs@PNC) was first synthesized by encapsulating of FeCo alloy into ZIF-8 and further carbonation of the composite. The FeCo NPs@PNC displays enhanced intrinsic oxidase-like activity compared to the individual FeCo NPs and porous nanocages (PNC). The FeCo NPs@PNC can catalyze the oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) to oxidized TMB (oxTMB) without H2O2, producing a blue color with a maximum absorption peak at 652 nm. The catalytic mechanism was investigated and it found that the intermediate (O2·-) produced from the catalytic process in the system of TMB-O2-FeCo NPs@PNC can accelerate the oxidation of TMB to oxTMB. However, ascorbic acid (AA) can reduce the oxTMB and result in a conspicuous blue color fading. Therefore, a novel colorimetric platform was constructed to quantify AA with the linear range of 0.5–28 μM and detection limit of 0.38 μM (at 3σ/m). Owing to the alkaline phosphatase (ALP) can catalyze the hydrolysis of AA 2-phosphate (AAP) into AA, ALP can also be quantified by the above method. And the linear range for ALP is 0.6–10 U L−1 and the limit of detection is 0.49 U L−1. The FeCo NPs@PNC also shows excellent stability and reproducibility. This study provides a new alternative oxidase mimetic on the basis of easily obtained metal-organic frameworks derivatives to replace the expensive natural enzymes and noble metal based nanoenzymes, which will show great potential in biological assays. (A) The synthesis process of FeCo NPs@PNC. (B) The obtained FeCo NPs@PNC have the intrinsic oxidase-like activity which can catalyze the oxidation of 3,3′,5,5′-tetramethylbenzidine (TMB) without H2O2 producing typical color reaction. Ascorbic acid (AA) can reduce the oxTMB and result in a conspicuous blue color fading. The alkaline phosphatase (ALP) can catalyze the hydrolysis of AA-2-phosphate (AAP) into AA. Therefore, novel colorimetric biosensing platform was constructed based on FeCo NPs@PNC-TMB system to quantify AA and ALP. [Display omitted] •FeCo NPs@PNC was first synthesized with enhanced intrinsic oxidase-like activity.•FeCo NPs@PNC can catalytically TMB oxidization in the absence of H2O2.•The oxidase-like activity stems from the synergistic effect of FeCo NPs and PNC.•The incorporation of FeCo NPs into MOFs solved the instability of FeCo NPs.•FeCo NPs@PNC-based novel colorimetric platform was built for AA and ALP detection.